Theo bài ra , ta có ab=40 => a2b2=402=1600
Khi đó
a4-2a2b2+b4=(a2)2-2.a2.b2+(b2)2
=(a2-b2)2 = (a2+b2)2-4a2b2
=1162-4.1600=7056
Các giá trị của ab = 40 thỏa mãn là :
a | 1 hoặc 40 | 2 hoặc 20 | 4 hoặc 10 | 5 hoặc 8 |
b | 40 hoặc 1 | 20 hoặc 2 | 10 hoặc 4 | 8 hoặc 5 |
Mà a2 + b2 = 116
=> a = 4 hoặc 10
=> b = 10 hoặc 4
Vậy
* Kết quả với a = 4 ; b = 10
a4 - 2a2b2 + b4
= 44 - 2 . 42 . 102 + 104
= 256 - 32 . 100 + 10000
= 256 - 3200 + 10000
= 7056
* Kết quả với giá trị a = 10 ; b = 4
a4 - 2a2b2 + b4
= 104 - 2 . 102 . 42 + 44
= 10000 - 2 . 100 . 16 + 256
= 10000 - 3200 + 256
= 7056
\(a^4-2a^2b^2+b^4=\left(a^2-b^2\right)^2=\left(a-b\right)^2\left(a+b\right)^2\)
\(=\left(a^2+b^2-2ab\right)\left(a^2+b^2+2ab\right)\)
\(=\left(116-2.40\right)\left(116+2.40\right)\)
\(=7056\)
ta có : \(\left(a^2+b^2\right)^2=a^4+2a^2b^2+b^4\)
=> \(a^4+b^4=\left(a^2+b^2\right)^2-2a^2b^2=116^2-2\left(40\right)^2=10256\)
=> \(a^4-2a^2b^2+b^4=10256-2\left(40\right)^2=7056\)